Association of Toll-like receptor 2 rs111200466 polymorphism with low serum levels of IL-33 in early childhood - Teräsjärvi Johanna T.; Toivonen Laura; Mertsola Jussi; Peltola Ville; He Qiushui (WILEY, 2023)
TLR2 is one of 10 human TLRs, which plays an important role in the recognition of pathogens and activation of the innate immunity via NF-κB pathway. NF-κB activation induces the expression of various pro-inflammatory genes. This study examines the effect of TLR2 polymorphisms on the production of blood pro-inflammatory cytokines in healthy Finnish children. One hundred forty-six children who participated in a prospective observational birth cohort study in Turku, Finland, were included. DNA samples were analysed by PCR-based sequencing for two common TLR2 polymorphisms (rs5743708 Arg753Gln; rs111200466–196 to –174del). Serum concentrations of IL-33, IL-31, IL-17A and IL-17F were measured by multiplex immunoassay and sST2 by ELISA in children at the age of 13 months. Children with variant type of TLR2 rs111200466 (ins/del or del/del) had significantly lower level of serum IL-33 (median, 0.00 pg/mL; IQR 0.00–17.60) than those with ins/ins type of TLR2 (19.81 pg/mL; IQR 0.00–51.78) (p = 0.0001). Almost all study subjects had serum concentrations of IL-17A, IL-17F and IL-31 below the detection limit and therefore not included in the final analyses. No differences in levels of above four cytokines and sST2 were found between TLR2 rs5743708 genotypes (GG and GA). Our results indicated that the TLR2 rs111200466 deletion was associated with a low level of serum IL-33, suggesting that the polymorphism may impair the production of IL-33.